Cercosporoid fungi from Thailand 3. Two new species of Passalora and six new records of Cercospora species - Jamjan Meeboon (2018)
This report is a part of a comprehensive study on cercosporoid fungi in Thailand, which started in October 2005. In this paper, twelve species of Cercospora and Passalora collected in Thailand are treated. Passalora barleriigena and P. sidaemysorensis are described here as new species. Six species of Cercospora are reported as new records for Thailand. Broussonetia papyrifera and Cucurbita moschata are reported associated with Cercospora for the first time. Four species of Cercospora represent Cercospora apii sensu lato.